Incidence of and modifiable risk factors for inadequate epidural analgesia in pediatric patients aged up to 8 years - Pangthipampai P. (2023)
Background and Aims: Postoperative pain in pediatric patients is one of most inadequately treated conditions. This study aimed to investigate the incidence of and modifiable risk factors for inadequate epidural analgesia in pediatric patients aged up to 8 years at Siriraj Hospital - Thailand's largest national tertiary referral center. Material and Methods: This retrospective study included pediatric patients aged 0-8 years who underwent surgery with epidural catheter during January 2015 to January 2020. Patients with missing data were excluded. Records from both the ward staff and the acute pain service were reviewed. All relevant data were extracted until the epidural catheters were removed. Results: One hundred and fifty pediatric patients were included. The median age was 29 months and the range varied from 12 days to 98 months on the day of surgery, and 86 (57.3%) were male. The incidence of inadequate epidural analgesia was 32%. Most patients (95.8%) had an unacceptably high pain score within 4 hours after arriving at the ward. Univariate analysis revealed direct epidural placement, the length in epidural space less than 5 cm, and postoperative leakage to be substantially higher in the inadequate pain epidural analgesia group. When those factors were included in multivariate analysis, only length in epidural space less than 5 cm was identified as an independent risk factor. Conclusion: The incidence of inadequate epidural analgesia in this pediatric study was 32%. Multivariate analysis showed length of catheter in epidural space less than 5 cm to be the only factor independently associated with inadequate epidural analgesia.